Forum: Conflict Delegation in Civil Wars. Issue 4 (2nd November 2021) - Karlén, Niklas; Rauta, Vladimir; Salehyan, Idean; Mumford, Andrew; San-Akca, Belgin; Stark, Alexandra; Wyss, Michel; Moghadam, Assaf; Duursma, Allard; Tamm, Henning; Jenne, Erin K; Popovic, Milos; et al.
Abstract: This forum provides an outlet for an assessment of research on the delegation of war to non-state armed groups in civil wars. Given the significant growth of studies concerned with this phenomenon over the last decade, this forum critically engages with the present state of the field. First, we canvass some of the most important theoretical developments to demonstrate the heterogeneity of the debate. Second, we expand on the theme of complexity and investigate its multiple facets as a window into pushing the debate forward. Third, we draw the contours of a future research agenda by highlighting some contemporary problems, puzzles, and challenges to empirical data collection. In essence, we seek to connect two main literatures that have been talking past each other: external support in civil wars and proxy warfare. The forum bridges this gap at a critical juncture in this new and emerging scholarship by offering space for scholarly dialogue across conceptual labels.